Determinants of employee engagement in Royal Malaysian Customs Department - Normalina, Abdul Manap (2019)
The main objective of this study is to examine the relationship between person-job fit, psychological safety, transformational leadership and perceived organizational support with employee engagement among customs officers in Kedah. To attain the objectives, a quantitative method was employed and data were collected through questionnaires. A total of 300 questionnaires were distributed to customs officers in Kedah and 241 questionnaires (80.3%) were received. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 22.0. The Pearson correlation analysis has confirmed significant and positive relationship between person-job fit, psychological safety, transformational leadership and perceived organizational support with employee engagement. Based on the findings it is suggested that customs officers should effectively enhance their person-job fit and psychological safety in order to increase their employee’s engagement. Other than that, Customs Department should effectively manage the transformational leadership and perceived organizational support as to boost up their employee’s engagement level.